A comprehensive eHealth implementation guide constructed on a qualitative case study on barriers and facilitators of the digital care platform CMyLife - Lynn Verweij; Yolba Smit; Nicole MA Blijlevens; Rosella PMG Hermens (BMC, 2022)
Abstract Background Substantial proliferation of eHealth has enabled a move in patient-centred cancer care from the traditional in-person care model to real-time, dynamic, and technology supported on-demand care. However, in general, the uptake of these innovations is low. Studies show that eHealth is helpful in providing patient empowerment through e.g. providing high quality and timely information, enabling self-monitoring and shared decision making, but dropout rates are high and guidance for optimal implementation is lacking. Aim To explore barriers to and facilitators for nationwide implementation and consolidation of CMyLife, a multi-component, patient-centred, digital care platform, and to construct a comprehensive implementation guide for launching digital care platforms in daily clinical practice. Methods The first qualitative case study of a digital care platform like CMyLife was performed including five focus group- and eighteen in-depth interviews with stakeholders. Data were collected using a semi-structured interview guide, based on the frameworks of Grol and Flottorp. Transcripts of the interviews were analysed and barriers and facilitators were identified and categorized according to the frameworks. An iterative process including participation of main stakeholders and using the CFIR-ERIC framework led to creating a comprehensive implementation guide for digital care platforms. Results In total, 45 barriers and 41 facilitators were identified. Main barriers were lack of connectivity between information technology systems, changing role for both health care providers and patients, insufficient time and resources, doubts about privacy and security of data, and insufficient digital skills of users. Main facilitators mentioned were motivating patients and health care providers by clarifying the added value of use of a digital care platform, clear business case with vision, demonstrating (cost) effectiveness, using an implementation guide, and educating patients and health care providers about how to use CMyLife. Based on these barriers and facilitators a clear and comprehensive implementation guide was developed for digital care platforms. Conclusion Several barriers to and facilitators for implementation were identified, a clear overview was presented, and a unique comprehensive implementation guide was developed for launching future digital care platforms in daily clinical practice. The next step is to validate the implementation guide in other (oncological) diseases.